2007
DOI: 10.1186/1472-6882-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salvia leriifolia Benth. root extracts on ischemia-reperfusion in rat skeletal muscle

Abstract: Background: Salvia leriifolia have been shown to decrease ischemia-reperfusion (I/R) injury in brain tissues. In this study, the effects of S. leriifolia aqueous and ethanolic extracts were evaluated on an animal model of I/R injury in the rat hind limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…It was shown that thymoquinone has a marked protective action against IR-induced gastric mucosal lesions (El-Abhar et al 2003). Moreover, it has protective effects against lipid peroxidation process during IRI in rat hippocampus (Hosseinzadeh et al 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that thymoquinone has a marked protective action against IR-induced gastric mucosal lesions (El-Abhar et al 2003). Moreover, it has protective effects against lipid peroxidation process during IRI in rat hippocampus (Hosseinzadeh et al 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Studies about anti-ischemic effect of aqueous extracts of S. leriifolia leaf and seed in rat hippocampus show that neural cell injury in all regions of the hippocampus was reduced following pretreatment of animals with aqueous seed extract [27]. The results of another investigations indicated that pretreatment with aqueous and alcoholic extracts of S. leriifolia root significantly reduced the elevated concentration of lipid peroxides in rat hippocampus and muscle following ischemia-reperfusion injuries because of its antioxidant properties [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as thrombosis and embolism and systemic blood reduction have pivotal role in induction of ischemia [1]. Cerebral ischemia leads to neurological disorders such as problems in movement and speech as well as neuropsychiatric defects such as cognitive dysfunction and apraxia, learning and spatial memory impairment [2]. High blood pressure, diabetes, smoking, alcohol drinking, dyslipidemia, hypercholesterolemia are main factors that increase risk of stroke [3].…”
Section: Introductionmentioning
confidence: 99%